P3 - A power-aware polling scheme with priority for bluetooth - Roy R.; Kumar M.; Sharma N.K.; Sural S. (My University, 2025)
We propose P3 - a polling scheme for Bluetooth in which a priority is assigned to each slave based on its packet arrival rate, available buffer space and the number of messages stored in the master buffer for that slave. Contrary to Round Robin (RR) polling, in our algorithm, a master can poll a slave more than once before it polls another slave. The main objective of this algorithm is to minimize power consumption and packet loss in each slave and increase the throughput while maintaining an acceptable level of delay. The proposed algorithm has a better performance compared to the existing polling schemes in case of diverse devices with different packet arrival rates or buffer sizes or both. Even in symmetric devices, it shows an improvement over the existing policies.